만성 거짓 장폐쇄로 진단한 상세불명의 복통 환자 증례 보고 - 하유빈; 장한솔; 신길조; Ha, Yu-bin; Jang, Han-sol; Shin, Gil-cho (대한한방내과학회지, 2021)
Objectives: This study examined a case of chronic intestinal pseudo-obstruction (CIPO) in an adult with unspecified abdominal pain.Methods: The patient was treated with herbal medicine, acupuncture, and moxa. Treatment progress was evaluated by follow-up monitoring of the intensity, frequency, and duration (in hours) of abdominal pain and body weight. Results: The average abdominal pain level on the Numerical Rating Scale (NRS) and its incidence decreased. The duration of pain was 15 hours maximum and 2.5 hours minimum. The body weight repeatedly increased and decreased but increased overall. Despite no remarkable findings from X-rays, air-fluid levels and coil-shaped folds of the small bowel were observed. Conclusions: Korean medical treatment based on a dialectic effectively relieved chronic abdominal pain and suspected CIPO-a disease that requires continuous management and therapeutic intervention.